برنامج مقترح لتطبيق نموذج الإشراف المدمج - طه الزبير حسين حسين, بانقا; بن دسمان شداد القثامي, محمد (جامعة الوادي - University of Eloued, 2019)
المستخلص هدفت الدراسة إلى وضع برنامج مقترح لتطبيق نموذج الإشراف المدمج في ضوء الاتجاهات الحديثة للإشراف التربوي، استخدم الباحثان المنهج الوصفي، ولجمع البيانات استخدم الباحثان أداة الاستبانة، وبلغ مجتمع الدراسة (1073) مُعلماً و(450) مُشرفاً في مكاتب التعليم بمدينة الطائف. اختار الباحثان عينة عشوائية بلغت(380) معلماً و(217) مُشرفاً. لتحليل البيانات استخدم الباحثان برنامج الحزم الحصائية وتوصلت الدراسة إلى العديد من النتائج أهمها: تبين أن الموافقة على أهداف البرنامج المقترح لتطبيق نموذج الإشراف المدمج جاءت بدرجة عالية، وكانت الموافقة على مكونات البرنامج المقترح جاءت أيضاً بدرجة عالية، وكانت الموافقة على الخطوات الاجرائية لتطبيق البرنامج المقترح للإشراف المدمج جاءت بدرجة عالية، وتوصلت الدراسة إلى وضع برنامج مقترح للإشراف التربوي في ضوء الاتجاهات الحديثة. وفي ضوء هذه النتائج يوصي الباحثان بالعمل على تطوير كفايات المشرفين التربويين على توظيف فكرة الإشراف المدمج، والعمل على تطبيق هذا البرنامج.ABSTRACT:The study aims to make a programmer for applying integrated supervision model in the light of the current trends for the educational supervision. The researchers used descriptive approach. For data collection, a questionnaire was used. The population of the study was (1073) teachers and (450) supervisors in at educational offices in Altayef city. A random sample of (380) teachers and (217) supervisors was chosen by the researchers. SPSS packages were used for data analysis. The study came out with a number of findings: one of which is that the agreement on the objectives of the programmer for applying the integrated supervision model was substantially high in degree. And the agreement on the components of the programmer was significantly high. As well as there was an extensively high degree of an agreement upon the procedural steps of the proposal of integrated supervision. The study, finally, concluded that there should be a programmer for educational supervision in the light of current trends. Based on the findings, the researchers recommended the following: developing the educational supervisors’ competences in order to adopt the idea of integrated supervision, and to implement the program.
من وجهة نظر المعلمين والمشرفيين التربويين في ضوء الاتجاهات الحديثة
مقال
Keywords: الإشراف المدمج، البرنامج المقترح، الإتجاهات الحديثة للإشراف; Integrated supervision; programmer; current trends of supervision